REDUKSI KANDUNGAN FOSFAT DALAM AIR LIMBAH DETERJEN MENGGUNAKAN SISTEM RAWA BAMBU - T Edy Sabli; Siti Zahrah (UIR Press, 2015)
Detergent is very dangerous for environment because of the water contaminated by detergent waste has potential as one of cause for cancer. The main formed material in detergent is Natrium Tripolifosfat (Na5P3O10) which a main cause of eutrofication on watar basin. A simple technology preventing water pollution is utilization of wet land. The swamp bamboo system is a novel innovation of wet land planted bamboo. This research was conducted unde laboratory scale in green house of Facuty of Agriculture, Riau Islamic University Pekanbaru. The completely random design was used with two factors, namely the beginning concentration detergent and the remaining time which consisted of four treatments and three replacation each. The treatments of konsentrasi awal deterjen were without detergent, 4, 8, and 12 g detergent/l of water and the remaining time consisted of 0, 10, 20, nd 30 days. As a result, the swamp bamboo system was able to process waste water to 12 g deergent/l of water (equvalent to 6.96 mg/l fosphat) with the remaining time was 30 days. Intereaction and main treatment had a significant effect on reducing phosphate conten in waste water.